Vilnius University, Department of Archaeology (from the establishment until year 1966) - Michelbertas, Mykolas (Archaeologia Lituana, 2010)
The aim of this article is to describe the history of the Department of Archaeology in Vilnius University from 1940 (the establishment) to 1966, when the department was integrated into the newly formed Lithuanian SSR Department of History. This article refers to the works of other authors, memorials and archival material.The circumstances surrounding the establishment of the Department of Archaeology go back to 1939, when the province of Vilnius was given back to Lithuania. Then the question of restructuring the Vilnius University also arose. On December 12th, 1939, the Parliament passed a highereducation law, which stated that the activities of the Lithuanian university would begin on December 15th, 1939, along with the opening of the Faculty of Humanities (FH) on the same day. For this reason the staff and students from the Vytautas Magnus University in Kaunas had to be moved to Vilnius. The relocation was set to begin after January 1st, 1940.The first meeting of the FH Council was held in Kaunas, on January 5th, 1940. It was decided to establish the Seminar of Archaeology with freelance docent J. Puzinas as its Head. The University museums of Archaeology and Ethnography were also entrusted to his care. Senior assistant Juozas Baldžius was elected to be his aid, while on February 15th, 1940, R. Volkaitė was elected as the museologist of the Archaeology museum. Thus began the career of Professor Ph. D. Jonas Puzinas in Vilnius University, the most famous interwar Lithuanian archaeologist and the pioneer of scientific archaeology in Lithuania.The work did not stop in June of 1940, after first Soviet occupation, although there were some changes. In autumn semester of 1940 the Department of Ethnics was divided into two separate Departments of Ethnography and Archaeology.Department of Archaeology in Vilnius University was established in September of 1940. On the September 20th J. Puzinas was elected to head of the Department of Archaeology and on January 1st, 1941, he was equated to a professor with a Ph. D. In the FH Council meeting on of June 5th, 1941, R. Volkaitė was elected assistant of the Department of Archaeology. So there were two academic researchers working in the Department at that time.The work did not cease during the years of Nazi Germany occupation. In the autumn of 1941 docent J. Puzinas was once again elected Head of Department of Archaeology. On December 5th he was presented as candidate for election of extraordinary professor. Until J. Puzinas fled to the West, he also was the Dean of FH (from June 26th, 1941) and the member of Vilnius University Senate (from August 7th, 1941).Teaching of archaeology disciplines in the University was not reserved to archaeology students only, but also to Ethnography and Lithuanian History students. During the war the Department did not conduct archaeological research so students did not have any fieldwork practice. The Department’s staff produced only a small amount of academic publications.In the summer of 1944 when the Red Army was approaching Vilnius, Professor J. Puzinas and his family fled to the West followed by M. Alseikaitė-Gimbutienė. However, the majority of archaeologists (former students of J. Puzinas), such as P. Kulikauskas, R. Volkaitė-Kulikauskienė and R. Jablonskytė-Rimantienė remained in Lithuania, continued their research and contributed to the preparation of specialists in the Department of Archaeology.At the beginning of second Soviet occupation in autumn of 1944, the Department of Archaeology became a part of the History and Philology Faculty. R. Volkaitė-Kulikauskienė and P. Kulikauskas worked in the Department.In 1947 the Departments of Archaeology, Ethnography and Art History in the History and Philology Faculty were reorganised into the Department of Museology. A few years later (in 1949) that Department was reorganised into the Department of Archaeology and Ethnography. R. Kulikauskienė became the Head of the Department and she held the post until 1962. P. Kulikauskas worked in this Department as anhourly paid scholar, whose primary job since 1948 was in the Institute of History of the Academy of Sciences. In 1951 one of the first post-war graduate archaeologists Aldolfas Tautavičius started to work in the Department of Archaeology as hourly paid scholar; it was his secondary job from March 17th, 1954 to April 30th, 1959. These three researchers taught the major archaeology courses at the university.The scientific work of the lecturers could not be fully fledged for one reason. By the secret decree of Lithuanian Communist Party’s (b) Central Committee, it was prohibited to mention the publications of researchers who fled to the West and were referred to as ‘motherland traitors’. Therefore the names of J. Puzinas, Latvian archaeologists V. Ginters, F. Balodis, E. Šturms and some German archaeologists did not appear in the Lithuanian archaeologists’ publications for the first post-war decades. There only were references to such publications as “Senovė”, “Gimtasai kraštas”, “Prussia” and others. For this reason some foreign researchers, who did not know the real situation, sometimes tauntingly wondered why Lithuanian archaeologists do not know the publications of their predecessors.Despite the difficulties in the post-war period, the Department of Archaeology and Ethnography successfully prepared professional archaeologists. 2 to 6 archaeologists graduated every year until 1962. Until that year 40 people received a degree in archaeology and part of them worked in various science institutions. In 1962 docent P. Kulikauskienė started to work at Institute of History of the Academy of Sciences. Docent P. Kulikauskas returned to the University and was the Head of the Department until 1966 when Department was closed.From 1948 to 1966 Vilnius University archaeologists did a lot of research on Lithuanian archaeological sites. University archaeologists were often organising expeditions together with the Institute of History of the Academy of Sciences.The most important sites worth noting are: Linksmučiai burial ground (Pakruojis district), Laiviai burial ground (Kretinga dictrict), Nemenčinė hillfort (Vilnius district), Migonys archaeological complex (Kaišiadorys district), Kunigiškės-Pajevonys hillfort (Vilkaviškis district). The monuments’ material, researched by the University archaeologists, was published in the form of scientific articles and monographs. In addition, a number of summarising articles were appeared in both Lithuanian and various USSR publications.R. Volkaitė-Kulikauskienė’s work “Lietuvos archeologiniai paminklai ir jų tyrinėjimai” (“Lithuanian Archaeological Monuments and Their Research”) has to be singled out. It was the first study book for students of archaeology, presenting the main types of archaeological monuments and some research results in the first half, while the second half dealt with heritage preservation and field research methodology.“Lietuvos archeologijos bruožai” (“The Features of Lithuanian Archaeology”) by P. Kulikauskas, R. Kulikauskienė and A. Tautavičius was published in 1961 and it was the biggest summarising work of Lithuanian archaeology yet, practically written by former and current University archaeologists. It was a very important event in the history of Lithuanian archaeology. The book described the research history of Lithuanian archaeological monuments, reviewed the sites from different periods with more detail than any previous publications, presented new data about the activities, crafts, trade relations, fortified and unfortified settlements of the Lithuanian people, discussed some questions about ethnic history of the Baltic tribes. This book not only summarised the research data of Lithuanian archaeological monuments, but also became a study book of Lithuanian archaeology.Concluding the Vilnius University Department of Archaeology (later – the Department of Archaeology and Ethnography) activities from 1940 to 1966, it must be noted that despite the war and post-war difficulties it prepared a lot of archaeology specialists for Lithuania. The staff of the Department of Archaeology made significant contributions investigating the sites of different archaeological periods, publishing and summarising the research material and preparing the most important publications about Lithuanian archaeology at the time.